Tolerância de cultivares de feijão-caupi ao déficit hídrico na fase germinativa: alterações fisiológicas, bioquímicas e citoquímicas - Oliveira, Letícia Kenia Bessa de (2020)
Northeast of Brazil is a semiarid region where there is a serious problem of drought. Thus, studies on physiology, cytochemistry and biochemistry of different cultivars may be a promising approach to identify the processes responsible for water stress tolerance. This research aimed to enlighten the physiological, cytochemical and biochemical mechanisms responsible for the delay or inhibition of germination and reserves mobilization in cowpea seeds under water deficit conditions. In the first section of this research, we evaluated the effects of water deficit (0, -0.1, -0.2, -0.4 MPa) on the germination and vigor of seeds of 14 cowpea cultivars. Furthermore, we selected two cultivars with differential tolerance to water deficit and the osmotic concentration that most affected the analyzed variables. In the second section, the imbibition curve of the two selected cultivars was characterized both with distilled water (0 MPa) and with PEG 6000 solution at the selected concentration (-0.2MPa). From the results we determined the time of imbibition in which the following experiments should be evaluated (0, 12, 24, 48 and 72 hours). In the third section, cytochemical analyzes were performed on cotyledons and embryonic axes according to the imbibition times. In the fourth section, we assessed the mobilization of reserves and the antioxidative defense system of cotyledon cells and embryonic axis of cowpea seeds. To achieve this, we set up a completely randomized experimental design with four replications, in the scheme of subdivided plots, in which the plots were defined by the 2 cultivars, the subplots by the 2 levels of osmotic potential (0 and -0.2MPa) and the sub-subplots by the 5 soak times. The cultivars BRS-Milênio and BRS-Pajeú were classified, respectively, as sensitive and tolerant to water deficit, both having followed a three-phase pattern of imbibition in the control treatment and in the solution with -0.2MPa, with the latter having a delay in the process water absorption. The cytochemical analysis of the embryos of both cultivars revealed cells with irregular shapes, thin cell walls and the presence of nuclei, also detecting the presence of starch in the cotyledons and protein bodies both in the cotyledons and in the embryonic axes. The water deficit delayed the mobilization of soluble carbohydrates and proteins from cotyledons to the embryo, provided a greater accumulation of N-aminosoluble and proline, both in cotyledons and embryonic axes, and caused considerable increases in the activity of antioxidant enzymes in cotyledons, mainly of ascorbate peroxidase (APX). The cultivar BRS-Pajeú showed higher levels of compatible solutes in the embryonic axes, as well as the one that showed greater activities of catalase and APX. Based on these results, it can be suggested that the cowpea seeds of the BRS-Pajeú cultivar have a higher water deficit tolerance level than the other cultivars, presenting a greater probability of resisting an environment with low water availability.